Network and Parallel Computing: 17th IFIP WG 10.3 International Conference, NPC 2020, Zhengzhou, China, September 28-30, 2020, Revised Selected Papers - IFIP WG 10.3 international conference, NPC; He, Xin; Shao, En; Tan, Guangming (Lecture Notes in Computer Science, 2021)
This book constitutes the proceedings of the 17th IFIP WG 10.3 International Conference on Network and Parallel Computing, NPC 2020, held in Zhengzhou, China, in September 2020.The 34 full and 7 short papers presented in this volume were carefully reviewed and selected from 95 submissions. They were organized in topical sections named: accelerator; AI; algorithm; architecture and hardware; big data and cloud; edge computing; emerging; network; and storage.